Effect of Leadership Style and Job Satisfaction on Simalungun District Health Office Employee Performance - Adrian K Tarigan; Anju B Nainggolan (Jurnal Mantik, 2020)
This study aims to find out the positive and significant influence between leadership style on employee performance, significant positive influence between job satisfaction on employee performance and significant positive influence between leadership style and job satisfaction together on the performance of simalungun district health office employees. The population of this study is all employees of simalungun regency health workers totaling 1384 people. The study sample was taken as much as 15% of the total population of 207 people. This research method is a quantifying method. Data collection in this study was conducted by providing questionnaires in the form of questionnaires Leadership style, job satisfaction and employee performance to the parties concerned. From the data analysis, it is known that there is a linear relationship of Leadership Style (X1) to Employee Performance (Y), : as evidenced by the value of FHitung 0.02 < FTabel 1.45 so that the regression equation is linear and it turns out that FHitung 29.14 > FTabel 3.88 so that the regression equation Y over X1 is meaningful. The large contributions (contributions) given by the Leadership Style (X1) to Employee Performance (Y) are relative donations of 57.83% and effective donations of 5.52%. The result of analysis of Leadership Style (X1) and Job Satisfaction (X2) data on Employee Performance (Y), it turns out that it has a form of linear relationship, namely: as evidenced by the value of FHitung 8.99 > FTabel(? = 0.05) 2.64 so that the regression equation is linear and meaningful. The large contribution (contribution) given by Leadership Style (X1) and Job Satisfaction (X2) to Employee Performance (Y) is 13.59% so that Employee Performance can be explained by Leadership Style and Job Satisfaction or in other words 86.40% explained by other variables partially.